2021
DOI: 10.31351/vol30iss1pp81-90
|View full text |Cite
|
Sign up to set email alerts
|

Assessment the Genotoxic Potential of Fluoxetine and Amitriptyline at Maximum Therapeutic Doses for Four-Week Treatment in Experimental Male Rats

Abstract: At any moment, the continuous usage of medications can accompanied by DNA damage and the accumulation of such damages can cause serious consequences. Antidepressants are long-term used drugs and the incidence of their genotoxic impacts cannot be excluded. Therefore, this work was designed to investigate the possible genotoxic effects of the commonly used antidepressants (fluoxetine and amitriptyline) in adult male rats. Detection of DNA damage in individual cells was assessed by comet and micronuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…With respect to kidney-shaped nuclei, these may occur from invagination of the nucleus [31] , whereas some studies have identified that they are caused by the same phenomena as micronuclei or binucleated cells [71] . Moreover, Al-Obaidi and Al-Shawi [72] reported findings similar to our results; they reported that FLX has genotoxic potential and can induce MN in polychromatic erythrocytes in the bone marrow of male rats. However, the origins of these morphological alterations of the nucleus have been found to arise from genotoxic events caused by exposure to xenobiotic agents [73] .…”
Section: Discussionsupporting
confidence: 90%
“…With respect to kidney-shaped nuclei, these may occur from invagination of the nucleus [31] , whereas some studies have identified that they are caused by the same phenomena as micronuclei or binucleated cells [71] . Moreover, Al-Obaidi and Al-Shawi [72] reported findings similar to our results; they reported that FLX has genotoxic potential and can induce MN in polychromatic erythrocytes in the bone marrow of male rats. However, the origins of these morphological alterations of the nucleus have been found to arise from genotoxic events caused by exposure to xenobiotic agents [73] .…”
Section: Discussionsupporting
confidence: 90%
“…Rats received Amitriptyline hydrochloride by oral gavage with dose (10 mg⁄kg⁄day) dissolved in 4 ml distilled water for four weeks ( Elsharkawy and Alhazzazi, 2016 , Abd AlObaidi et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%